1993
DOI: 10.1785/bssa0830051574
|View full text |Cite
|
Sign up to set email alerts
|

Site effect evaluation using spectral ratios with only one station

Abstract: The spectral ratio technique is a common useful way to estimate empirical transfer function to evaluates site effects in regions of moderate to high seismicity. The purpose of this paper is to show that it is possible to estimate empirical transfer function using spectral ratios between horizontal and vertical components of motion without a reference station. The technique, originally proposed by Nakamura to analyze Rayleigh waves in the microtremor records, is presented briefly and it is discussed why it may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
11

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 912 publications
(107 citation statements)
references
References 9 publications
0
96
0
11
Order By: Relevance
“…For soft soil sites, the local site effect should also be considered. It is known that the rough estimation of the soil amplifications can be calculated by using H/V spectral ratio approach (Ameri et al, 2011;Castro et al, 1997;Field & Jacob, 1995;Ji, 2014;Lermo & Chávez-García, 1993, 1999Yalcinkaya et al, 2012). For general sites, as there is no obvious amplification phenomenon of vertical ground motion in the horizontal amplification frequency band (Castro et al, 1997), the amplification characteristics of Note.…”
Section: Site Effectmentioning
confidence: 99%
“…For soft soil sites, the local site effect should also be considered. It is known that the rough estimation of the soil amplifications can be calculated by using H/V spectral ratio approach (Ameri et al, 2011;Castro et al, 1997;Field & Jacob, 1995;Ji, 2014;Lermo & Chávez-García, 1993, 1999Yalcinkaya et al, 2012). For general sites, as there is no obvious amplification phenomenon of vertical ground motion in the horizontal amplification frequency band (Castro et al, 1997), the amplification characteristics of Note.…”
Section: Site Effectmentioning
confidence: 99%
“…paper, the windowing function proposed by Konno and Ohmachi (1998) was employed for smoothing the obtained Fourier spectrum in a range of 0.5 and 15 Hz, while the smoothing constant was taken as 20 (Sun et al, 2013;Fu and Li, 2017;Kkallas et al, 2018). In our applications, we adopt the κ 0 filter in the form of κ 0.033036 + 0.0008401×R, as shown in Figure 2, and employed the H/V spectral ratio approach (Lermo and Chávez-García, 1993) to estimate the local site amplification in the Jiuzhaigou earthquake .…”
Section: Attenuation Parametermentioning
confidence: 99%
“…From the mid-1900s, thanks to systematic measurements of microtremors, it was found that the properties of the ground as inferred from the characteristics of these microtremors can be used to determine the seismic factor related to earthquake-proof construction designs [72,73]. The HVSR technique for microtremor studies has gained much popularity over the past years [37,[74][75][76].…”
Section: A Simple Procedures To Refine the Soil Profilementioning
confidence: 99%